Antioxidant and anti-diabetic potential of the green synthesized silver nanoparticles using Martynia annua L. root extract - Megha B. Abbigeri; Bothe Thokchom; Sapam Riches Singh; Santosh Mallikarjun Bhavi; B.P. Harini; Ramesh Babu Yarajarla (Nano TransMed)
The weed Martynia annua traditionally known as Kakanasika is annual herbaceous plant known for its multiple medicinal properties such as anthelmintic, analgesic, antipyretic, antibacterial, anti-convulsant, anti-fertility, antinociceptive, antioxidant, CNS depressant and wound healing activity. The aqueous root extract of M. annua was subjected to qualitative analysis, revealing the presence of terpeniods, indicative of its rich phytochemicals composition. Utilizing a green synthesis approach, silver nanoparticles (AgNPs) were successfully synthesized from the plant extract. Characterization through UV-Visible spectroscopy, FTIR, DLS, and SEM/EDX confirmed the formation of AgNPs with polygonal morphology and an average size of 64 nm, with the PDI of 0.385. Additionally, the AgNPs demonstrated moderate stability, evidenced by a zeta potential of −21.6 mV. Evaluation of the synthesized AgNPs focused on their anti-diabetic potential. The green synthesized R-AgNPs were potent antioxidant agents. They exhibited significant inhibition of alpha amylase, a pivotal enzyme in carbohydrate metabolism, suggesting their efficacy as anti-diabetic agents. Moreover, the AgNPs enhanced glucose uptake by yeast cells, indicating their promising therapeutic role in managing diabetes mellitus. This study highlights the pharmacological importance of M.annua, particularly its aqueous root extract, in the eco-friendly synthesis of AgNPs with potential therapeutic implications. Further investigation into the mechanism of action and clinical efficacy of these AgNPs in diabetes management is warranted.